Equality in Indonesian higher education for international students: A narrative inquiry - Hastowohadi, Hastowohadi; Sayid Ma’rifatulloh (Journal of International Students, 2025)
This study aims to underpin equality issues of international students learning in Indonesian higher education institutions by engaging with this issue and identifying how international students in Indonesia reshape their learning trajectory by providing quality and equitable education for international students. We implemented a narrative inquiry research design; we interviewed six international students from various backgrounds of the study to determine the institutional equality perception of their learning surroundings. By using emotional geography and language appraisal, we undergo the analysis to dig out their experiences and passionate encounters when they studied in Indonesia. The recommendations of the findings will be beneficial in improving Indonesian university quality from social and cultural facets, as well as the institutional system. In short, embracing diversity, equity, and inclusiveness to engage international students’ participation and capacity is pivotal in reshaping their identity.